Beberapa Kelainan Genetik yang Bersifat Protektif terhadap Infeksi Malaria - Syamsudin Syamsudin (JURNAL ILMU KEFARMASIAN INDONESIA, 2007)
Resistance to malarial infection is dependent on the development of an immune response by the host and to a varying extend, a certain innate characteristics possessing protective value against infection. Innate resistance is not always absolute and genetically determined factors, but instead can act to reduce the severity of infection and improve survive. Mechanism of action resistance to malarial infection will be discussed in this article.